Potassium fulvic acid alleviates salt stress of citrus by regulating rhizosphere microbial community, osmotic substances and enzyme activities - Zhang, Manman; Li, Xiaoya; Wang, Xiaoli; Feng, Jipeng; Zhu, Shiping (Frontiers in Plant Science, 2023)
Salt stress damage to plants has been becoming a global concern for agriculture. The application of potassium fulvic acid (PFA) is a promising strategy to alleviate the damage to plants and improve soil quality. However, the study of PFA on plant growth and rhizosphere microbial community remains limited. In this study, microcosmic experiments were conducted to verify the effect of PFA on citrus. Trifoliate orange (Poncirus trifoliata), the most important citrus rootstock, was used to evaluate the effect of PFA on salt damage. The results showed that PFA significantly increased the contents of chlorophyll a, chlorophyll b and carotenoid by 30.09%, 17.55% and 27.43%, and effectively avoided the yellowing and scorching of leaves under salt stress. Based on the results of two-way ANOVA, the mitigation of salt stress on trifoliate seedlings primarily attributed to the enhancement of protective enzyme activities, K+/Na+ ratio and the contents of soluble sugar, soluble protein and proline. Moreover, PFA enhanced neutral protease (S-NPT), sucrase (S-SC) and urease (S-UE) of rhizosphere soil and improved soil nutrition status. The abundance of Bacillus, a kind of rhizosphere beneficial bacteria, was improved by PFA under salt stress, which was mainly associated with the increased activities of S-NPT, S-SC and S-UE. Overall, the application of PFA showed great potential for the alleviation of salt damage on citrus.